The Relationship Between Using Green Tea in Preventing Skin Aging : A Literature Review - Febby Pebrianti; Ummi Malikal Balqis (STIKES Hesti Wira Sriwijaya, 2025)
Introduction: Aging is a natural biological process in humans. Skin aging can be caused by both intrinsic and extrinsic factors. These factors lead to visible signs of aging, such as facial wrinkles, reduced elasticity, and changes in skin texture. Extrinsic aging is associated with environmental factors and is characterized by thinning of the epidermis and fine lines. In contrast, intrinsic aging, which is primarily caused by sun exposure, is marked by deep wrinkles, sagging skin, and hyperpigmentation. Flavonoids in green tea play a role in reducing free radicals, which are one of the main triggers of skin aging. Method: This study used a literature review method based on selected articles discussing the relationship between green tea and skin aging prevention. Results: The review identified three main themes from the selected articles, indicating that green tea has a positive effect in preventing skin aging. Conclusion: Based on the literature review, it can be concluded that green tea has beneficial effects in preventing skin aging. The antioxidant content, particularly flavonoids, helps reduce the impact of free radicals, which are major contributors to the aging process. Therefore, green tea can be considered a natural option to support skin health and delay visible signs of aging.